Prehospital neuromuscular blockade post OHCA: UK's first paramedic-delivered protocol. (2nd May 2020) - Durham, Mark; Westhead, Pete; Griffiths, David; Lyon, Richard; Lau-Walker, Margaret
Abstract : Background: Since 2016, critical care paramedics from the South East Coast Ambulance Service have offered neuromuscular blockade to patients for ventilatory/airway control after cardiac arrest. Aims: To examine the first cases of paramedic-delivered neuromuscular blockade, and evaluate the prevalence of its use and safety. Methods: Retrospective service evaluation of patients receiving post-arrest paralysis during the study period from 1 April 2016 until 31 July 2017. Findings: The study included 127 patients. The mean age of administration was 63 years, mean weight was 80 kg (SD: 19 kg), dose was 1 mg/kg and median time from rocuronium administration to hospital was 32 minutes (IQR 20–43 minutes). Three patients (2.3%) experienced a minor adverse incident. There were no major airway complications, nor other significant adverse incidents. Thirty-seven patients (31%) survived to discharge. Conclusion: From this patient group, paramedic-administered rocuronium in intubated patients who have experienced a cardiac arrest and a return of spontaneous circulation appears to be safe, but further interventional research is required to determine whether this improves patient outcomes.